Hyperleukocytosis in Newborn: A Diagnosis of Concern - Parvez, Yusuf (Springer India, 2013)
Leukocytosis is well recognised in neonate; mostly it is physiological but the counts rarely exceed 30,000/mm(3). Hyperleukocytosis defined as WBC count of more than 100,000 mm(3) is rare and imposes a diagnostic challenge and should be investigated for leukaemia, leukocyte adhesion defect and myeloproliferative disorders. We report a classic case to highlight this entity.